Analysis of suspended sediment distribution in Lamteng waters, Nasi Island, Aceh Besar District, Indonesia. Issue 1 (May 2021) - Arsyami, Y F; Purnawan, S; Yuni, S M; Setiawan, I
Abstract: The presence of sediment in the water column that moves without touching the bottom is known as suspended sediment. The distribution of suspended sediments in the coastal area is strongly influenced by river flows and ocean currents. Thus, this study aims to determine the distribution pattern and level of suspended sediment concentration in Lamteng waters, Nasi Island, Aceh Besar District. This research was conducted in October and December 2019. Samples were taken from 15 stations from the research location, each in October and December. Total suspended solids (TSS) samples were analysed using the Gravimetric method, in which the TSS value distribution was presented using the Natural Neighbour method. The results showed that the average TSS value in October was higher than in December. TSS in Lamteng waters shows a value that exceeds the quality standard value based on the Ministry of Environment.